Defect characterisation from limited view pipeline radiography - Haith,MI; Huthwaite,P; Lowe,MJS (NDT & E INTERNATIONAL, 2016)
This work presents a method of characterising pipeline defects using a small number of radiographs taken at different angles around the pipe. The method relies on knowledge of the setup geometry and use of multiple images, and does not require calibration objects to be included in the setup. It is aimed at use in situations where access is difficult such as in subsea pipeline inspections. Given a set of radiographs, a background subtraction method is used to extract defects in the images. Using a ray tracing algorithm and knowledge of the experimental setup, the range of possible locations of the defect in 3D space is then calculated. Constraints are applied on potential defect shapes and positions to further refine the defect range. The method is tested on simulated and experimental flat bottomed hole defects and simulated corrosion patch defects with lateral and axial sizes ranging from 12.5 to 33.8 mm and thickness between 3 mm and 16 mm. Results demonstrate a good, consistent ability to calculate lateral and axial defect dimensions to within ±3 mm of the true size. Defect thickness calculations are more difficult and as such errors are more significant. In most cases defect thickness is calculated to within 4 mm of the actual value, often closer. Errors in thickness are due to overestimation, meaning the calculation could be used to place a maximum limit on potential defect size rather than as an actual estimate of the thickness. This would still be useful, for example in deciding whether a defect requires further investigation.